D. 26.10.7, 26.10.2, 26.10.4 e l’accusatio suspecti tutoris: la competenza del praetor tutelaris e del praefectus urbi sulla remotio tutoris e quella del praetor urbanus sulla missio in possessionem rei servandae causa - Arcaria, Francesco (Tesserae iuris, 2023)
The purpose of the article is the resolution of delicate problems regarding the competence of some judicial bodies of the ordo iudiciorum and of the cognitio extra ordinem in the matter of accusatio suspecti tutoris and remotio tutoris posed by three fragments coming from the first of the books de omnibus tribunalibus of Ulpian.